Towards an Integrated Assessment Framework: Using Activity Theory to Understand, Evaluate, and Enhance Programmatic Assessment in Integrated Content and Language Learning - Paretti, Marie C. (Journal of Academic Writing, 2013)
This article uses activity theory to analyse two different portfolio approaches as tools for programmatic assessment of Integrated Content and Language (ICL) programs. The two approaches include a) a model in which students construct portfolios by selecting artifacts from a range of different contexts and provide reflective commentary, and b) a model in which the portfolio consists of major textual artifacts produced across a design project, with no reflective component. Activity theory provides a tool to explore what these models can offer in terms of an assessment of the integration of content and language in disciplinary contexts, where texts serve to mediate the ongoing work of a discipline. By highlighting the work that texts do in context as well as the access to student meta-knowledge afforded by each portfolio, activity theory provides a means to understand the strengths and limitations of both models. Perhaps most importantly, it points to the need for portfolios to include well-designed reflections that can support both student learning and effective programmatic assessment.